Transformational leadership and project success: The mediating role of trust and job satisfaction - Fareed, Muhammad Zeeshan; Su, Qin; Almutairi, Mubarak; Munir, Kashif; Fareed, Mian Muhammad Sadiq (Frontiers in Psychology, 2022)
Transformational leadership (TFL) impacts on project and organizational success are well established. However, many underlying factors that make transformational leadership effective are still missing. Therefore, we formulated hypotheses and tested the mediating role of trust (TS) and job satisfaction (JS) in linking TFL to project success (PS). A time-lagged methodology was used to collect quantitative data using a structured questionnaire from 326 project manager-team member dyads working in Pakistan’s public sector. Our results showed that TS, JS and TFL significantly impacted project success. Moreover, we found that TS and JS mediate the relationship between TFL and PS. These findings highlight the importance of trust and job satisfaction as mechanisms that translate transformational leadership into the success of projects for organizations.